Understanding the complex chromatin dynamics in primary human neutrophils during PMA-induced NET formation - Atteberry, Brandi; Berman, Benjamin P.; Kelly, Theresa K.; Cayford, Justin (Frontiers in Immunology, 2024)
Primary human neutrophils play a pivotal role in innate immunity, mainly through the formation of neutrophil extracellular traps (NETs) in a process known as NETosis. This cell-death pathway is crucial for combating infections but is also implicated in many inflammatory diseases such as sepsis, systemic lupus erythematosus, rheumatoid arthritis, and others.The study presented here investigates chromatin dynamics during NET formation by stimulating primary human neutrophils with phorbol 12-myristate 13-acetate (PMA). We adapt the ATAC-seq (Assay for Transposase-Accessible Chromatin using sequencing) method to isolated neutrophils and characterize a time-dependent chromatin response.We find that chromatin accessibility patterns are consistent across individual donors and most chromatin changes occur within 30 minutes, with many continuing across the 90 minutes assessed in this study. Regulatory regions gaining accessibility are associated with activity of pathways that have been implicated in NOX-dependent NET formation.Our findings enhance the understanding of the chromatin changes underlying NET formation and also identify potential early-acting targets for modulating this process in inflammatory diseases.